2022
DOI: 10.3390/jcm11247406
|View full text |Cite
|
Sign up to set email alerts
|

Central versus Peripheral Postcardiotomy Veno-Arterial Extracorporeal Membrane Oxygenation: Systematic Review and Individual Patient Data Meta-Analysis

Abstract: Background: It is unclear whether peripheral arterial cannulation is superior to central arterial cannulation for postcardiotomy veno-arterial extracorporeal membrane oxygenation (VA-ECMO). Methods: A systematic review was conducted using PubMed, Scopus, and Google Scholar to identify studies on postcardiotomy VA-ECMO for the present individual patient data (IPD) meta-analysis. Analysis was performed according to the intention-to-treat principle. Results: The investigators of 10 studies agreed to participate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Additionally, hemodilution, non-pulsatile perfusion and other factors can influence the microcirculation of important tissues and organs. These reasons lead to a significant increase in lactic acid concentration 23 . Severe hyperlactic acidemia decreases myocardial contractility and cardiac output, and also reduces the cardiovascular response to vasoactive drugs, further affecting tissue perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, hemodilution, non-pulsatile perfusion and other factors can influence the microcirculation of important tissues and organs. These reasons lead to a significant increase in lactic acid concentration 23 . Severe hyperlactic acidemia decreases myocardial contractility and cardiac output, and also reduces the cardiovascular response to vasoactive drugs, further affecting tissue perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with Mahmoud U. Sani's observation [ 11 ]. Interestingly, despite peripheral arterial cannulation being the exclusive method for ECMO cannulation via the peripheral arteries, a study conducted by Fausto Biancari et al examined the cannulation methods of 1269 patients requiring postcardiotomy VA-ECMO, which found that central arterial cannulation was associated with a higher risk of in-hospital mortality compared to peripheral arterial cannulation [ 12 ]. Our ECMO team will pay attention to and collect cases with both types of cannulation in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the slightly higher survival rate (27.3% vs. 22.2%) seen in patients with central cannulation can be attributed to the use of larger cannulas and increased flow [33]. The benefits of central cannulation in post-cardiotomy adult patients are being discussed, and contrasting findings have been found in the literature [34,35]. Peripheral ECMO may have the benefit of a lesser risk of bleeding [36] but pose a risk of limb ischemia [37].…”
Section: Discussionmentioning
confidence: 99%